Implementation of Customary Marriage of Nuaulu Tribe People as Civic Culture in Sepa Country, Amahai District - Sopalatu, Najwa; Sialana, Fatimah; Tuharea, Jumiati (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Traditional marriages in the Nuaulu tribe community usually begin with a request or proposal made by the male family through a messenger or spokesperson who is commonly referred to as ruetawamana. This was done on the basis of the young man and the girl who had made an agreement to marry. So that what parents do is just to fulfill rituals and carry out the provisions of applicable customary law. The rituals in the traditional marriage process which are usually carried out at the time of marriage are usually accompanied by an exchange of property between the man and woman and then followed by a blessing ritual led by the chief of the tribe by praying specifically and to unite and bind as proof that they are truly married. it is true that husband and wife who are legal in the eyes of customary law are to cover both parties with the sarongs that have been prepared. The author of this thesis discusses "Implementation of Nuaulu Tribe Traditional Marriage as Civic Culture in Negeri Sepa, Amahai District". The problems discussed in this study are: 1. the process of implementing Nuaulu tribal marriages as Civic Culture. 2. the meaning of traditional marriage for the Nuaulu tribe. The type of research used in this research is descriptive qualitative with observation and interview techniques and using qualitative analysis techniques. The results of this study indicate that in the process of carrying out a traditional marriage, the Nuaulu tribe must fulfill several conditions, including that someone who wants to perform the marriage should provide a dowry in the form of a human head. The Nuaulu people use this method to choose a son-in-law as proof of the man's virility, but over time At that time, this tradition was replaced because it caused unrest in other communities so that it was replaced in the form of old dishes and money as dowry. The process of implementing marriage as Civic Culture is one of a series of life cycles that everyone always goes through and therefore needs to be celebrated because it is one of the local cultures that is still being preserved. The meaning of traditional marriage for the Nuaul tribe is something sacred and has become a tradition from ancient times until now. as a tribute to the ancestors.